Distribution And Degradation Of Pesticide In Paddy Field Ecosystem In Penaga, Seberang Prai Utara - Abdul Rashid, Mazratul Amyra (2017)
Rivers are the primary sources of water for farming purposes in Malaysia. A study was carried out in paddy plantation and the irrigation channels at Mukim 5, Penaga, Seberang Perai Utara, Pulau Pinang. The study was to determine the surface water quality in rice paddy plantation and its surrounding areas and also to determine the distribution and degradation of pesticide residues in water samples from the adjacent water body of a paddy field. The six parameters of physical and chemical characteristics of surface water quality were measured and analyzed were pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (NH3-N) and suspended solids (SS).